2016
DOI: 10.1111/isj.12102
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the influence of absorptive capacity and ambidexterity on the process of business model change – the case of on‐premise and cloud‐computing software

Abstract: The increasing popularity of Software as a Service has strongly affected the established business model of on‐premise enterprise software. Software as a Service has distinctive characteristics of disruptive innovations that typically create several difficulties for incumbent firms, in particular with regard to adapting business models. To date, however, little empirical understanding exists regarding the dynamics of business model change – a topic of special importance to the highly dynamic software industry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 102 publications
(144 reference statements)
1
76
0
9
Order By: Relevance
“…Network effects are therefore an important factor in social media platforms that utilise Web 2.0 technology and are an important mechanism of change. This is in line with previous research where technology is identified as an important element to explain business model dynamics (Mason and Spring, 2011); Kranz, Hanelt, and Kolbe. 2016).…”
Section: Business Modelssupporting
confidence: 92%
“…Network effects are therefore an important factor in social media platforms that utilise Web 2.0 technology and are an important mechanism of change. This is in line with previous research where technology is identified as an important element to explain business model dynamics (Mason and Spring, 2011); Kranz, Hanelt, and Kolbe. 2016).…”
Section: Business Modelssupporting
confidence: 92%
“…Apart from that, researchers examined the fundamental impacts of the shift from delivering on-premise IT applications to cloud services with regard to business models (e.g., [1,2,45]). In addition, scholars have dealt with the process of transforming an on-premise business model to a cloud business model (e.g., [46][47][48]). Ebel et al [49] built and evaluated a software tool to support the business model creation.…”
Section: Introductionmentioning
confidence: 99%
“…Gambardella and McGahan (2010) point to the importance of "commercialization capabilities," including an orientation toward marketing, and installing and selling integrated solutions based on broader customer insights. Along similar lines, Kranz, Hanelt, and Kolbe (2016) argue for the role of "balanced capabilities" to avoid misalignments with respect to the necessary timing and scope of BM change. Achtenhagen et al (2013) identify the need for "critical capabilities," such as experimentation, a balanced utilization of resources, and coherence between leadership, organizational culture and employee commitment, in value creation processes.…”
Section: Bmi Capabilitiesmentioning
confidence: 97%